The effectiveness and safety of neurosurgical treatment via retrosigmoid approach in elderly patients with trigeminal neuralgia. (October 2021) - Sun, Junwei; Zhu, Jialin; Zhang, Li; Yu, Yanbing
Highlights: Elderly TN patients treated with retrosigmoid approach have satisfying pain outcome. It is safe for elderly patients to treat trigeminal neuralgia via retrosigmoid approach. MVD + PSR may be a better choice for elderly TN patient. Abstract: Objective: The purpose of this study was to evaluate the effectiveness and safety of retrosigmoid approach in treating older patients with trigeminal neuralgia (TN). Methods: In this retrospective study, 49patients (65 and over, elderly group) and 85 patients (under 65, young group) underwent MVD, MVD + PSR or PSR for idiopathic TN from July 2009 to December 2018. The two groups were compared for immediate, long-term pain outcome and postoperative complications. All perioperative data were collected from medical records and telephone interviews. The pain outcomes were assessed with the Barrow Neurological Institute (BNI) pain score. Results: The length of follow-up was 13.2 to 124.8 months. 91.8% of the elderly patients and 89.4% of the young patients achieve "Good" immediate pain outcome (BNI I-II), the proportion were 73.5% and 60.0%, respectively, in long-term pain outcome. No statistically significant differences existed in the immediate and long-term pain outcome between the elderly and young patients (P = 0.768 and P = 0.116, respectively). In the grouping analysis, whether in the pure MVD group or the PSR-related group, the immediate and long-term pain outcomes of elderly patients were not significantly different from those of younger patients. Meanwhile, there was no significant difference in the incidence of neurological and non-neurological complications between two groups. Conclusions: Compared with young patients, the treatment for TN in elderly patients via retrosigmoid approach has the same favorable pain outcome. The safety of this procedure for elderly TN patients is similar to that in young patients.